Molecular view by Fourier transform infrared spectroscopy of the relationship between lactocin 705 and membranes: Speculations on antimicrobial mechanism - Castellano, Patricia Haydee (2007)
Lactocin 705 is a bacteriocin whose activity depends upon the complementation of two peptides, termed Lac705α and Lac705β. Neither Lac705α nor Lac705β displayed bacteriocin activity by itself when the growth of sensitive cells was monitored. To obtain molecular insights into the lactocin 705 mechanism of action, Fourier transform infrared spectroscopy was used to investigate the interactions of each peptide (Lac705α and Lac705β) with dipalmitoylphosphatidylcholine liposomal membranes. Both peptides show the ability to interact with the zwitterionic membrane but at different bilayer levels. While Lac705α interacts with the interfacial region inducing dehydration, Lac705β peptide interacts with only the hydrophobic core. This paper presents the first experimental evidence that supports the hypothesis that Lac705α and Lac705β peptides could form a transmembrane oligomer. From the obtained results, a mechanism of action of lactocin 705 on membrane systems is proposed. The component Lac705α could induce the dehydration of the bilayer interfacial region, and the Lac705β peptide could insert in the hydrophobic region of the membrane where the peptide has adequate conditions to achieve the oligomerization.